ARTFM: Augmented Reality Visualization of Tool Functionality Manuals in Operating Rooms - Kleinbeck, Constantin; Schieber, Hannah; Andress, Sebastian; Krautz, Christian; Roth, Daniel (Proceedings - 2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops, VRW 2022, 2022)
Error-free surgical procedures are crucial for a patient's health. However, with the increasing complexity and variety of surgical instruments, it is difficult for clinical staff to acquire detailed assembly and usage knowledge leading to errors in process and preparation steps. Yet, the gold standard in retrieving necessary information when problems occur is to get the paperbased manual. Reading through the necessary instructions is time-consuming and decreases care quality. We propose ARTFM, a process integrated manual, highlighting the correct parts needed, their location, and step-by-step instructions to combine the instrument using an augmented reality head-mounted display.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Human computer interaction (HCI); Human-centered computing; Interaction paradigms; Mixed/augmented reality